Pengelolaan Konten Digital Media Sosial Untuk Meningkatkan Engagement Rate Instagram Telkom Regional Iv - Oktorizal, Roby; Sujana, Aprianti Putri; Kurniawan, Ady Purna (eProceedings of Applied Science, 2024)
Telkom Indonesia utilizes social media such as Instagram to increase engagement and audience reach. As a state-owned company in the information technology sector, Telkom Indonesia Regional 4 Central Java and DIY runs the Digital Amoeba innovation program which incubates employee ideas to create digital innovations. One of the startups from this program, Level Up, provides training for pupils and students to support national digitalization and increase global competitiveness. This project aims to increase active interaction between Telkom Regional IV and its followers on Instagram in order to build closer and more involved relationships. By using general descriptive methods, the results obtained show an increase in Engagement Rate and number of followers. The implementation of the strategy has proven successful in increasing interaction with followers, increasing the number of followers, and obtaining positive responses in the form of likes and views. Keywords— Instagram, Digital Content, Social Media